A raia de Ribacôa: perspetivas de investigação compreendendo o período de 1762-1960 - Mendonça, Maria Isabel Lopes de (CEM – Cultura, Espaço & Memória, 2021)
The research about the dialectics of the organization of the settlements in Ribacôa’s ray, comprising the period between 1762 and 1960, arises from the systematization and interpretation of the territory’s architecture in a tensional dialogue with its border condition. The mentioned region (roughly confined to the municipalities of Figueira de Castelo Rodrigo, Almeida and Sabugal) will thus constitute the main aspect of analysis and problematization related with contemporary landscape modeling, which is coordinated with state actions aimed according the productive and economic possibilities of the region. The discourse about the action of several agents over the centuries will recover aspects of the evolution of human occupation that constitue a methodological basis for understanding the territorial process. In a perspective of holistic understanding, it will be demonstrated that exploratory incursions including primary sources and the theoretical field must be complemented by local surveys, namely those showing the human settlements in articulation with its vital space that integrates the water structures, the constructions supporting the military actions as well as the circulation system, the industries and the farms.